Correlates of Cortisol in Human Hair: Implications for Epidemiologic Studies on Health Effects of Chronic Stress - Wosu, Adaeze C. (2013)
Assessment of cortisol concentrations in hair is one of the latest innovations for measuring long-term cortisol exposure. We performed a systematic review of correlates of cortisol in human hair to inform the design, analysis and interpretation of future epidemiologic studies. Relevant publications were identified through electronic searches on PubMed, WorldCat, and Web of Science using keywords, “cortisol” “hair” “confounders” “chronic” “stress” and “correlates.” Thirty-nine studies were included in this review. Notwithstanding scarce data and some inconsistencies, investigators have found hair cortisol concentrations to be associated with stress-related psychiatric symptoms and disorders (e.g., PTSD), medical conditions indicating chronic activation of the hypothalamic-pituitary-adrenal axis (e.g., Cushing´s syndrome) and other life situations associated with elevated risk of chronic stress (e.g., shiftwork). Results from some studies suggest that physical activity, adiposity, and substance abuse may be correlates of hair cortisol concentrations. In contrast to measures of short-term cortisol release (saliva, blood, and urine), cigarette smoking and use of oral contraceptives appear to not be associated with hair cortisol concentrations. Studies of pregnant women indicate increased hair cortisol concentrations across successive trimesters. The study of hair cortisol presents a unique opportunity to assess chronic alterations in cortisol concentrations in epidemiologic studies.